Analisis Integrasi Pasar Parsial untuk Komoditas Daging Ayam Broiler antar Berbagai Kabupaten/Kota di Provinsi Jambi - Adesra, Irfan; Firmansyah, Firmansyah; Idris, Nahri; Hoesni, Fachroerrozi (Ekonomis: Journal of Economics and Business, 2024)
This research aims to determine the spatial market integration of broiler chicken meat commodities between various districts/cities in Jambi Province. The analysis method used is the VAR (Vector Autoregression) / VECM (Vector Error Correction Model) model. There is partial market integration in the long and short term for broiler chicken meat commodities between various regencies/cities in Jambi Province so that the price of broiler chicken meat in regencies/cities in Jambi Province influences each other not only in the current period but in relation to prices 1 to 2 days before. There is short and long-term spatial market integration for broiler chicken meat in districts/cities in Jambi Province. The price of broiler chicken meat in Jambi City causes changes in the price of broiler chicken meat in Batang Hari Regency, Kerinci Regency, Merangin Regency and West Tanjung Jabung Regency, and vice versa.